Marginality or provinciality? Pskov and Ivangorod at the intersection of Russia's trans-border relations - Andrey Makarychev (Danish Institute for International Studies (DIIS), 2004)
My intention in this paper is to analyze the state of trans-border relationship between Russia, on the one hand, and Latvia and Estonia, on the other, in terms of interplay between central and non-central actors. Two basic concepts – that ones of marginality and provinciality – will be used as points of departure and compared with each other. Each of these concepts develops its own narrative and a discursive strategy. In some instances, these narratives may smoothly complement each other; and yet in other occurrences, they conflict in a manner that fuels “a battle of the story”. Conceptually, the paper is based upon the ideas developed by Noel Parker, Vladimir Kaganski and Dmitry Zamiatin that are adjusted to the study of trans-border relations. The paper argues that the Pskov oblast and the city of Ivangorod may be regarded as provinces and margins simultaneously, depending on the contextual frame under consideration. As parts of domestic conceptualizations, they would be better characterized as provinces, while entering the transnational scene they may be labeled as margins.
Keywords: 330